Acceptability and preliminary effectiveness of a text messaging intervention to reduce high-risk alcohol use among adults 50 and older: an exploratory study. Issue 2 (17th February 2022) - Kuerbis, Alexis; Behrendt, Silke; Arora, Varnica; Muench, Frederick J.
Abstract : Purpose: Prevalence rates of older adults (OA, 50+) with high-risk alcohol use are rapidly growing. Barriers to intervention persist for OA. Mobile interventions, specifically short message service (SMS, also known as text messaging), provide an opportunity to overcome such barriers. The purpose of this paper is to explore the acceptability and preliminary effectiveness of four SMS intervention conditions compared to mobile assessment only among OA (50–65 years old, n = 49) who drink at high-risk levels compared to younger adults (YA, 21–49 years old, n = 102). Design/methodology/approach: Within and between age group differences at baseline and end-of-treatment (12 weeks) were explored. Generalized linear modeling was used to test age by receipt of any SMS intervention (compared to assessment only) effects across health outcomes. Effect sizes and visual analyses were generated to assess for age by type of SMS interactions. Findings: Both age groups reported intervention satisfaction. Two-thirds elected to continue receiving SMSs after treatment concluded. Descriptively, SMS groups demonstrated reduced drinking across age groups at end-of-treatment compared to mobile assessment only, though slightly larger effects were found for YA than for OA. Age significantly moderated the receipt of any SMS intervention only for depression (i.e., older age weakened the therapeutic effect). Of all the SMS types, tailored messages outperformed the other conditions on drinking outcomes for both age groups. Depression, craving and alcohol problems responded to gain-framed messages among OA and loss-framed messages among YA. Research limitations/implications: The findings of this paper suggest that SMS is acceptable and potentially effective across age groups. Further adaptation of SMS across age groups could enhance its effectiveness. Originality/value: This is the first paper to explore the impact of older age on the efficacy of text messaging as an intervention for hazardous alcohol use.